Evaluasi Validitas dan Kualitas Soal Pilihan Ganda Mata Pelajaran IPAS Kelas VI SDN 159 Palembang - Lidya Febrianti; Reska Ayu Natasya; Priska Utami; Raihana Raihana; Afrianto Afrianto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the validity and quality of multiple-choice items in the Science and Social Studies (IPAS) subject for sixth-grade students at SDN 159 Palembang. The evaluation seeks to ensure that the test items used in assessments can accurately and fairly measure student competencies. A quantitative approach with descriptive methods was applied. The sample consisted of 30 multiple-choice questions from the odd semester examination in the 2024/2025 academic year. Data were analyzed using SPSS version 26. The findings show that, in terms of content validity, 24 items (80%) were categorized as valid, while 6 items (20%) were invalid. Regarding item difficulty, 10 items (33.33%) were classified as easy, 15 items (50%) as moderate, and 5 items (16.67%) as difficult. In terms of discrimination power, 6 items (20%) had excellent discrimination, 9 items (30%) were good, 8 items (26.67%) were fair, and 7 items (23.33%) had poor discrimination. For distractor effectiveness, 68 distractors (75.56%) were effective, while 22 (24.44%) were ineffective due to lack of selection by students. In conclusion, the overall quality of the IPAS multiple-choice questions used in SDN 159 Palembang is fairly good, particularly in terms of validity and difficulty. However, improvements are needed for items with low discrimination power and ineffective distractors to enhance the assessment's ability to measure learning outcomes accurately